The Sufi Symbol in Arabic Literature through the Efforts of Modernizers" A Study in Methodology - Rese. Huda Hameed Naif; Dr . Thaer Abdul-Majeed Al-Azari (Journal of College of Education, 2025)
Sufi literature has received a large number of studies that have come down to us, and they are studies with different curricula and different procedural tools, and these studies, even if they differed in their curricula and the way they dealt with the topics they dealt with, but they agreed on one fact, which is the richness of the Sufi heritage, its fertility and its ability to openness and renewal.In this research, we chose one of the academic studies that dealt with the most important issues raised in Sufi literature, which is the Sufi symbol. In this study, we aspire to address the thesis of the researcher “Anas Majid Shakhouth "The Sufi Symbol in Arabic Literature through the Efforts of the Modernists", who highlighted in His dissertation focused on studies that dealt with the Sufi symbol among researchers and critics, adopting an approach based on exposition, description and criticism in addressing these studies.The research dealt with the topic of the thesis; By examining its approach and how it is employed, and the extent of the researcher's commitment to applying this approach based on the procedures of the descriptive approach to the study of the Sufi text, especially the symbolic one; As the symbol paved the way for creating a creative text that is not devoid of originality and distinction.
Keywords: The Sufi Symbol, Sufi Literature, Methodology, Descriptive Methodology.